Single-Institution Experience With Nononcologic Total Femoral Replacement - Ryan Ouillette, MD; Kevin Chen, BA; Matthew Dipane, BA; Alexander Christ, MD; Edward McPherson, MD; Alexandra Stavrakis, MD (Arthroplasty Today)
Background: Revision hip and knee arthroplasty volume continues to rise, and total femur replacement (TFR) remains a key salvage option in patients with extensive bone loss. Prior research has demonstrated mixed results of this procedure, and this study aimed to characterize the outcomes of nononcologic TFR in one of the largest single-center modern series. Methods: A retrospective analysis was conducted on 23 nononcologic TFR procedures performed on 22 patients between 2012 and 2021. Primary outcomes included TFR revision rate and indication for revision, while secondary outcomes included overall reoperation rate, complications, patient ambulatory status, and assistive device requirements. Results: The average age at time of TFR was 65.7 years, with periprosthetic fracture (65.2%) and periprosthetic joint infection (34.8%) as predominant indications. More than half of patients (52.2%) required TFR revision, primarily due to periprosthetic joint infection (75.0%). Despite a high complication profile, only 1 patient underwent limb amputation and there was only 1 mortality during the study period. Overall, 63.6% of patients were ambulating (assisted or unassisted) at final follow-up. Conclusions: Nononcologic TFR remains a viable limb-salvage option for patients undergoing revision arthroplasty with extensive bone loss. Despite a notable revision rate and infection risk, the majority of patients maintain or regain ambulatory function, emphasizing the procedure’s role in preserving limb function. Clinicians should weigh potential complications when considering TFR, emphasizing patient counseling and risk mitigation strategies.